Fundraising nestátní neziskové organizace - Zouharová, Bohumila (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce se zabývá financováním neziskových organizací. Zaměřuje se na možné způsoby a metody fundraisingu. Praktická část obsahuje analýzu výnosů organizace Junák – svaz skautů a skautek ČR, středisko Jedovnice, možné zdroje financování a návrhy na způsoby získání finančních prostředků.

This thesis deals with the financing of nonprofit organizations. It focuses on the possible ways and methods of fundraising. The practical part contains an analysis of revenues Scout organization - association of scouts and guides of the Czech Republic, the centre „Jedovnice“, possible funding sources and proposals for ways of obtaining financial resources.
Fundraising for the Non-profit Organisation
Keywords: Neziskový sektor; nezisková organizace; občanské sdružení; fundraising; fundraisingové metody; dotace; projekt.; Non-profit sector; non-profit organization; voluntary association; fundraising; fundraising methods; grant; project.